Effect of Gum Arabic (Acacia senegal) on Growth Performance, Carcass Quality and Health of Clarias gariepinus Juveniles - Falaye, Augustine Eyiwunmi; Abah, Abel; Sule, Shakiru Okanlawon (Universitas Airlangga, 2024)
The effect of Gum Arabic (GA) on growth, carcass quality, blood parameters, gut morphometry, and organ histology of African catfish Clarias gariepinus was studied. Five isonitrogenous diets with inclusion levels of GA at 0 g/100 g (GA0; control), 5 g/100 g (GA5), 10 g/100 g (GA10), 15 g/100 g (GA15), and 20 g/100 g (GA20) were formulated in a 40% crude protein diet. Juveniles of C. gariepinus with average weight (7.35±0.48 g/fish) were stocked at 13 fish/25 L of water for 12 weeks in a completely randomized design and fed at 3% body weight daily. Growth indices showed GA10 improved the mean weight gain (69.88±8.89 g) and specific growth rate (2.76±0.14 %/day) while at (GA15); (GA20) growth was depressed. Carcass quality revealed dietary levels were superior to control with GA10 significantly different (p < 0.05) amongst treatments in protein and fat content. Hematological profile showed variations; erythrocyte indices compared to control, while plasma chemistry of aspartate aminotransferase, alkaline phosphatase, and alanine aminotransferase showed no difference (p > 0.05). Gut morphometrics varied with no particular pattern. At inclusion above GA5 the gill, liver, and kidney were affected histologically with no changes in the intestines of all treatments. Diet supplemented with gum arabic at 10 g/100 g improved indices of performance of C. gariepinus juveniles in this study.